Analisa Metode Seo (Search Engine Optimization) dalam Bisnis pada Website Mastercahaya.Com - Agus Cahyo Witono agus (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The purpose of this study is to find out how the SEO method in business is carried out on the mastercahaya.com website. SEO (Search Engine Optimization) is an optimization technique on a website according to the rules of the Google algorithm. Every business needs alternative marketing steps that support the achievement of marketing targets. The research method used by the researcher is descriptive quantitative, with the method of collecting observation data on the website. The results showed that all values on the mastercahaya.com website for existing indicators increased after consistent SEO optimization was carried out.